ANALISIS LAPORAN KEUANGAN ON LINE PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - MOHAMAD ADAM (Program Studi Magister Manajemen FE Unsri, 2015)
The purpose of this study is to analyze the financial statements on line. Contribution of this study are: first, can provide relevant information for decision makers and credit investments. Second, as a business communications medium between management and external users related changes in financial position and cash flows of the company. Third, give an idea about their ability to generate profits and cash flows of the company. Fourth, give a picture of the company from one period to the next related growth or decline of the company. In conclusion are first, the analyze the financial statements on line needs its own way. By analyzing the financial statements can be found on line and reliable investment position and become the benchmark for preparing plans for further investment. Second, the financial statements on line only gives an overview of the development of investment, but of the financial statements on line can be known whether the stock market is quite large compared promising investment income in the form of another.